Study on Customer Value and Experiential Marketing Towards Word of Mouth at "Nine Cafe" Semarang - Ismanto, Fiderius; Sulistyaningsih, Sri; Martini , Martini; Jatmiko, M. Roby; Rahmah, Wa Ode Sitti Nur (Economics and Business International Conference Proceeding, 2024)
This study investigates how customer value and experiential marketing influence word of mouth (WOM) for "NINE CAFE" in Semarang. Conducted via a survey of 100 frequent cafe customers, the research employs regression analysis to demonstrate that both customer value and experiential marketing exert a statistically significant and positive impact on WOM. These findings underscore the importance of enhancing customer value and cultivatingpositive experiences to stimulate customer recommendations. The implications suggest that focusing on improving customer perceptions and creating memorable experiences can effectively boost WOM, potentially leading to increased customer loyalty and business growth for "NINE CAFE". Such strategies could be crucial for cafes and similar businesses aiming to leverage WOM as a marketing tool in competitive environments.